2017
DOI: 10.1007/s10518-017-0289-1
|View full text |Cite
|
Sign up to set email alerts
|

RC infilled building performance against the evidence of the 2016 EEFIT Central Italy post-earthquake reconnaissance mission: empirical fragilities and comparison with the FAST method

Abstract: Damage data on low-to-mid-rise Reinforced Concrete (RC) buildings, collected during the UK Earthquake Engineering Field Investigation Team post-earthquake reconnaissance mission on the August 24 Central Italy earthquake, are employed to derive empirical fragility relationships. Given the small dataset, the new data distributions are used for the Bayesian update of fragility functions derived for the L'Aquila earthquake (same seismic region and similar construction typologies). Other properties such as number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…Del Gaudio et al (2017) have derived empirical fragility curves based on the large database of post L'Aquila 2009 Earthquake damage surveys conducted by the Italian Civil Protection (Dolce and Goretti 2015) on RC buildings. De Luca et al (2018) have used the observed damage for infilled RC structures in the aftermath of the 24th August 2016 Amatrice Earthquake for Bayesian updating of existing empirical fragility curves for central Italy. Rosti et al (2018) have used the database of damage data collected after the 2009 L'Aquila (Italy) earthquake, to derive damage probability matrices for several building types representative of the Italian building stock.…”
Section: A Brief History Of Empirical Fragility Assessment For Buildimentioning
confidence: 99%
“…Del Gaudio et al (2017) have derived empirical fragility curves based on the large database of post L'Aquila 2009 Earthquake damage surveys conducted by the Italian Civil Protection (Dolce and Goretti 2015) on RC buildings. De Luca et al (2018) have used the observed damage for infilled RC structures in the aftermath of the 24th August 2016 Amatrice Earthquake for Bayesian updating of existing empirical fragility curves for central Italy. Rosti et al (2018) have used the database of damage data collected after the 2009 L'Aquila (Italy) earthquake, to derive damage probability matrices for several building types representative of the Italian building stock.…”
Section: A Brief History Of Empirical Fragility Assessment For Buildimentioning
confidence: 99%
“…Another aspect to be considered when deriving fragilities from observational data is the spatial distribution of the dataset. Several studies have shown that spatially inhomogeneous datasets (i.e., buildings concentrated in areas where the range of variation of PGA is limited) can lead to inconsistent results (De Luca et al 2018). In these cases, Bayesian updating procedure of existing fragility curves should be adopted (Singhal and Kiremidjian 1998;Miano et al 2016).…”
Section: Empirical Fragility Estimates For Masonry School Buildingsmentioning
confidence: 99%
“…Bayesian Updating (BU) techniques are effective alternatives to traditional statistical methods when dealing with small or spatially inhomogeneous observational damage datasets. Several studies have suggested the adoption of Bayesian techniques to update preexisting fragility curves (e.g., Singhal and Kiremidjian 1998;Miano et al 2016;De Risi et al 2017;De Luca et al 2018). As mentioned in the introduction, a Bayesian approach has been also used by Didier et al (2017) in the context of Nepal, but the analysis was solely focused on residential buildings and did not include schools.…”
Section: Bayesian Updating Of Existing Fragility Models For Differentmentioning
confidence: 99%
“…Paulay and Priestley, 1992) and the commonly observed post-earthquake damage on RC structures (e.g. Elnashai and Di Sarno, 2008;Palermo et al, 2017;De Luca et al, 2018). For each of them, Table 3 provides guidance on the selection of the alternatives.…”
Section: Performance Modifiermentioning
confidence: 99%